Sosialisasi Marketing Plan Dengan Digital Marketing Untuk Meningkatkan Pemanfaatan Rawat Inap di Puskesmas Gempol - Rakhmawati, Fitria (Jurnal Abdimas Jatibara, 2022)
This community service activity has the aim of restoring the trust and interest of the Gempol community to return to utilizing inpatient services at the Gempol Health Center. The COVID-19 pandemic has created feelings of fear and anxiety in the community; this is the cause of the problem of decreasing interest in utilizing inpatient services at the Gempol Health Center. To overcome this issue, it can be circumvented by making marketing strategies, both directly and by digitalization. The method of socialization that we do is through presentations and discussions about SOP and animated videos used in marketing strategies. The results were achieved in the form of changes in perception and increased interest in the use of inpatient services for BPJS patients at Gempol Health Center.